ANALISIS KOORDINASI KERJA ANTARA DESA DENGAN KECAMATAN DAN KABUPATEN : STUDI DI SUNGAI KAKAP, KABUPATEN KUBU RAYA - Makrina Ciptayuni (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This study departs from the results of governance issues in the field of coordination through the organization of government in the Office of the Great Village River District weeds Snapper Kubu Raya district. This type of research used in this study is descriptive qualitative descriptive qualitative research because in trying to present the information gathered verbally in the form of the detail is not in the form of numbers or formulas. Since the purpose of this method to interpret human behavior is significantly better about themselves or others. The purpose of this study to know the Village Government Coordination weeds in the Great River District Kubu Raya district. So the results of this study In order to achieve efficiency, effectiveness and productivity of development, needs to be a feasibility study on the importance of coordination between relevant agencies in implementing regional development tasks. Coordination in the implementation is a process to develop and maintain a good relationship between physical activity and non-activity-physical. Keywords: Division of Labour, Cooperation Among Apparatus, coordination to Top.